Representing Libras Poetry on Video (Altre Modernità, 2019)
Fernanda de Araujo Machado has taught Brazilian Sign Language (Libras) and literature of Brazilian sign Language at the Federal University of Santa Catarina, Brazil. since 2014. She completed her Masters degree in 2013 on Symmetry in Sign Language poetry and defended her PhD on anthologies of Libras poetry in 2017.